2022
DOI: 10.1108/srj-06-2021-0238
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship between intellectual capital, corporate governance and corporate social responsibility

Abstract: Purpose Intellectual capital, corporate governance (CG) and corporate social responsibility (CSR) are generally considered three essential pillars to enhance firms’ performance in the developed world. However, in developing countries such as Vietnam, these pillars have not received sufficient attention from practitioners. In addition, this study aims to investigate the interrelationship between these three essential pillars and their combined effects, in the Vietnamese context. Design/methodology/approach Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 73 publications
2
7
0
3
Order By: Relevance
“…the company's efforts to disclose information on social responsibility or Islamic social reporting in an action that is in accordance with the system of norms, values, and public beliefs. Companies that implement good governance will provide greater corporate social responsibility disclosures or Islamic social reporting (Vo et al, 2022). The results of this study are in line with research conducted by Susbiyani et al (2022), Amran et al (2017) and Fadhila et al (2020) which state that the Islamic Governance Score has a positive influence on the disclosure of Islamic Social Reporting.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…the company's efforts to disclose information on social responsibility or Islamic social reporting in an action that is in accordance with the system of norms, values, and public beliefs. Companies that implement good governance will provide greater corporate social responsibility disclosures or Islamic social reporting (Vo et al, 2022). The results of this study are in line with research conducted by Susbiyani et al (2022), Amran et al (2017) and Fadhila et al (2020) which state that the Islamic Governance Score has a positive influence on the disclosure of Islamic Social Reporting.…”
Section: Discussionsupporting
confidence: 89%
“…The test results above indicate that the education of the sharia supervisory board has no effect on the disclosure of Islamic social reporting. This can happen because the degree of education level held by the sharia supervisory board is in various fields, not necessarily in the field of accounting which results in not all understanding the theory and practice of disclosing social responsibility (Vo et al, 2022). The results of this study are in line with research conducted by Setiawan (2020), Meutia et al (2019) and Nugraheni (2018) which found that the education of the sharia supervisory board had no effect on the disclosure of Islamic social reporting.…”
Section: Discussionsupporting
confidence: 80%
“…The physical and intellectual resources of a company are just two examples of its resources; its intellectual assets are its brainpower. They are a critical component, an advantageous resource, and sustainability depends on effective administration of them (Vo et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modal intelektual sebagai sumber daya yang tidak berwujud terdiri atas tiga elemen utama berupa modal struktural, modal sumber daya manusia, dan modal pelanggan yang menambah nilai aset (Vo et al, 2022). Modal sumber daya manusia berkaitan dengan pengetahuan, keterampilan, kemampuan, profesionalisme karyawan, dan karakteristik pribadi lainnya.…”
Section: Pendahuluanunclassified